Exploring the Intricate Interplay: Language and Thought in Philosophy Review (Scripta : English Department Journal, 2023)
This article aims to gain a clear and thorough understanding of the interconnection between languages and thought from a philosophical point of view. By exploring the interplay between language and thought, the study seeks to deepen understanding of how language functions as a tool for expressing and communicating thoughts, as well as how its is influenced by underlying cognitive processes. Moreover, the study highlights the significance of philosophy in examining and analyzing the intricate dynamics between language and thought. Language, thought, and philosophy are the three things that affect each other and the relationship is deeply rooted. To collect data in this study, researchers used qualitative methods by using relevant literatures, summaries and quotations of books, journals, news, and other sources so that they can be used as references for other researchers and educators, the novelty of this research is to identify the importance of meaning and references in language acquisition and communication. The study provides valuable insights and contributes to the broader field of research on the relationship between language, thought, and philosophy.
Keywords: Intricate Interplay; Language; Thought; Philosophy